Mengoptimalkan Lalu-Lintas Perbelanjaan dengan Mengatur Derajat Kepentingan Antar Etalase - Tan, Hendy Tannady (Bina Nusantara University, 2012)
The high rate of retail industry growth absolutely needs good attention and well-constructive improvement. We often see that the consumer waste their time to shop in super market. With Data Mining and its relation with association function, it is expected to give inputs and contribution for the revolution of placing procedure of display case layout in every retail businesses, either in big supermarket or the small one. The result of this research is that the association pattern was gained among several display-case objects, and the distance between display cases is the determined variable of the implementation of association tabulation.